Coupled nonlinear elasticity, plastic slip, twinning, and phase transformation in single crystal titanium for plate impact loading. (June 2019) - Feng, B.; Bronkhorst, C.A.; Addessio, F.L.; Morrow, B.M.; Li, W.H.; Lookman, T.; Cerreta, E.K.
Abstract: High purity single crystal titanium (Ti) under shockwave loading in plate impact experiment is modeled and simulated, with help of the finite element. A thermodynamically consistent system of equations is formulated in the frame of large deformation to consider material anisotropy, rate dependence, and multi-physics including nonlinear elasticity, dislocation based plastic slip, deformation twinning, and phase transformation. A novel kinematics is proposed to consider phase transformation in the α twin variants and also to consider the dislocation based slip in all of components of parent material, primary twins and the ω phase. The thermodynamically consistent driving forces for plastic slip, twinning, and phase transformation are developed based upon the second law of thermodynamics. For nonlinear elasticity, the stiffness matrix is dependent on the volume fractions of all components, and the volumetric part of Cauchy stress is obtained from the nonlinear equation of state. Dislocation based plastic slip in multi-variant and multiphase heterogeneous materials is developed and interactions of dislocations among all slip modes are taken into account. A mechanism for dislocation density evolution during twinning and phase transformation is proposed. The shock loading along the [0001] and [ 10 1 ¯ 1 ] directions of single crystal high purity Ti is investigated computationally. Very good correspondence between simulation and experiment is obtained, which includes pole figures, volume fractions of components, free surface velocity, peak pressure, and phase transformation pressure. Multiple experimental phenomena are interpreted based upon the progression of dislocation slip, deformation twinning, and phase transformation. In compression with the [ 10 1 ¯ 1 ] crystal, a higher volume fraction in the primary twins but a lower secondary twin volume fraction in the [0001] crystal in experiment was observed. The higher propensity for phase transformation occurs in the [0001] crystal is reproduced. In addition to material texture, distributions of temperature, stresses, and plastic strains dependent on the impact loading directions are revealed.